WHEN TABLES TURN: DISCURSIVE CONSTRUCTIONS OF WHITES AS VICTIMS OF AFFIRMATIVE ACTION IN A POST-APARTHEID SOUTH AFRICA - Wambugu, Jacob Ngunyi (PINS-Psychology in Society, 2026)
This paper considers how white people in post-apartheid South Africa manage to oppose affirmative action policies, yet still inoculate themselves from accusations of racism. Data was collected from six focus groups comprised of 40 white university students. These students were asked to discuss their perceptions of affirmative action policies in the current South African context. These students regarded affirmative action policies as unfair and unethical whilst also constructing themselves as victims of these policies. It is argued that in an effort to manage the dilemma of opposing affirmative action policies without appearing to be racist, white people use the strategy of appealing to discourses of "Othering" and fairness and justice. These discourses help nurture a construction of victimhood. This paper draws attention to how this victimhood is appropriated and how it serves as an insulating device against claims of racism that might be aimed at opponents of affirmative action policies.